Comparing inequalities in the labour market from a segmentation perspective - López Roldán, Pedro (2020)
The purpose of this chapter is to carry out a comparative analysis of labour markets in Europe and Latin America from the perspective of segmentation in order to explain the processes of social inequality that arise in the workplace, in light of recent trends in global socio-economic changes. The chapter proposes two main objectives. The first is to perform a comparative descriptive analysis of the main features of labour markets among 60 European and Latin American countries. The second objective is to propose a model of comparative analysis of labour inequality from the theoretical perspective of the segmentation of the labour market and structural heterogeneity. We will focus our analysis by selecting two countries, Spain and Argentina, which both underwent a late development of capitalism. The following general hypothesis is formulated: Spain and Argentina, having clearly differentiated features in economic structure, level of development, institutional frameworks and socio-historical processes, show common dynamics in the structuring of the capitalist labour market between a primary and secondary segment. Using equivalent databases on the workforce a typology of segmentation of employment is constructed that show, in addition to the specificities of each country, the similarities in the structuring of the labour market.